ANALISIS KEPUTUSAN KONSUMEN MEMBELI BERAS PREMIUM DAN NON PREMIUM DI KOTA BATURAJA KABUPATEN OKU - Anthony Purawijaya; Yunita Sari; Fifian Permata Sari (Media Bina Ilmiah, 2025)
This study aims to analyze consumer decisions in purchasing premium and non-premium rice in Baturaja city. The research method used is a random chance method where consumers who buy premium and non-premium rice are used as samples for analysis. The sampling method used is proportional stratified random sampling with 30 samples of consumers who buy premium rice and 30 samples of consumers who buy conventional or non-premium rice. The results of the study analyzed using logit analysis showed that the variables of premium rice price (X1), rice quality (X2) and rice consumption experience (X2) have a significant effect on the purchase of premium rice by consumers.